Injectable Col-Ⅰ/CS hydrogel enhances bone regeneration in mice tibial mono-cortical defect with impaired osteogenesis. (August 2022) - Lu, Jiarui; Xu, Ruoman; Chen, Yanan; Chan, Laiting; Feng, Xin; Lin, Lichieh; Yao, Yichen; Hu, Xiaoli; Zhang, Xiaolei
Abstract: Bone possesses the intrinsic capacity for regeneration as part of the repair process in response to injury. However, bone repairing capacity can be affected by many conditions, including genetic disorders. The development of a smart biomaterial to improve bone regeneration for patients with impaired osteogenesis remains a challenge. In this study, a thermosensitive hybrid hydrogel scaffolds, which was based on collagen I (Col-Ⅰ) and chondroitin sulfate (CS) and crosslinked with genipin (Col-Ⅰ/CS hydrogel), was prepared. The Col-I/CS hydrogel was presented with features favoring clinical application, including injectability, mild reaction conditions, rapid cross-linking, and biocompatibility. According to the in vitro assessments, the osteogenic differentiation and biomineralization of pre-osteoblasts and bone marrow mesenchymal stem cells were promoted by the presence of Col-I/CS hydrogel, along with the enhanced molecule/protein expressions of osteogenic markers. To impair osteogenesis in vivo, the conditional knockout of Stat3 in osteoblast precursors (Osx-cre; Stat3 f/f, Stat3 CKO) was generated via the Cre-loxP recombination system using Osterix-Cre (Osx-Cre) transgenic mice. The tibial mono-cortical defect was made on both wild-type and Stat3 CKO mice. Compared with the control, the healing of bone defect was significantly improved by use of the hydrogel, including the increase of the quality and mass of bone in wildtype mice, and the improvement of the bone mass in Stat3 CKO mice. The Col-Ⅰ/CS hydrogel was able to enhance bone regeneration, even under the condition of genetically impaired osteogenesis, showing a promising potential for therapeutic application. Graphical Abstract: ga1